A Mathematical Model to Evaluate the Kinetics of D-glucose and D-fructose Fermentations by Saccharomyces bayanus at Increasing Ethanol Concentrations - Zinnai, A.; Venturi, F.; Sanmartin, C.; Quartacci, M.F.; Andrich, G. (South African Journal of Enology and Viticulture, 2016)
In the cellar, slow and stuck fermentations occurring during winemaking are often successfully solved by the addition of yeast strains like Saccharomyces bayanus. The kinetic behaviour shown by S. bayanus during alcoholic fermentation was investigated using a mathematical model previously tested for S. cerevisiae, in order to show which of the six functional parameters of the model differed significantly with the yeast population. Although some parameters (hexose fractions converted to ethanol and glycerol) did not change, the kinetic constant related to the inactivation rate of the yeast population showed by S. cerevisiae assumed a value significantly higher (approximately 50-fold) than that observed for S. bayanus, while this latter population was ten times less affected by ethanol than S. cerevisiae. Although no remarkable differences could be found between the ability shown by the two yeast populations to convert hexoses (D-glucose and D-fructose), the tolerance for ethanol accumulation changed strongly. The conversion rate of these two hexoses by S. bayanus was affected less (about ten thousand-fold) by ethanol than that of S. cerevisiae.